Pengaruh Model Pembelajaran Problem Based Learning Berbasis Hypnoteaching Terhadap Hasil Belajar Siswa Pada Materi Cahaya - Surbakti, Mariana; Laia, Indah Septa. A. (Jurnal Visi Eksakta, 2022)
This study aims to determine the effect of Hypnoteaching-based or Problem Based Learning? (PBL) learning methods on student learning outcomes on the subject of light. This type of research is a pre-experimental study with the population of this study being all students of class X MIA I. The sample in this study consisted of one class that was selected directly with the purposive technique. The research instrument used was an observation sheet on student learning activities and an objective test in the form of multiple choice which had been tested for validity. Based on the results of observations of student learning outcomes, the average pretest score was 34.86 with a standard deviation of 1.33 and the post-test average value was 84.86 with a standard deviation of 1.17. From the results through the t-test of the two samples correlated for pretest and posttest data for = 0.05 and dk = 70, it is obtained that tcount = 24.72 and ttable = 1.67, which shows tcount > ttable, then Ha is accepted and Ho is rejected. Based on the results of this study, we can conclude that there is a significant effect of the Hypnoteaching-based PBL learning model on the learning outcomes of class X MIA I students. The relationship of each variable is indicated to have a significant effect through regression test analysis with the results obtained Y = 42.6 + 0.52 X Based on the results of the correlation test with the acquisition of the value of the correlation coefficient r = 0.73 which indicates that the relationship between the two variables is strong.